Currículo intercultural na fronteira: um estudo sobre a política e as práticas de currículo na fronteira Brasil/Bolívia do estado de Rondônia - Uchôa, Márcia Maria Rodrigues (2019)
This research aims at studying Policy and Practices of School Curriculum in cities of the state of Rondônia, Brazil that border Bolivia . Our goal is to analyze the curricular policy adopted by the State Department of Education of Rondônia (SEDUC-RO) and how its implementation unfolds within the curricular practices of the public schools of the border towns: Nova Mamoré and Guajará-Mirim, in order to provide a reflection on the presence of Bolivian culture in the curricula of the educational institutions of these locations.The lack of inclusion of Bolivian culture in the school curriculum, which has contributed to the spread of prejudice and discrimination against the Bolivian immigrant, constitutes our research problem. Our research hypothesis that approaches curriculum from an intercultural standpoint, opens perspectives for the development of social justice by recognition and affirmation of an overpowered and peripheral culture in the school context. The theoretical framework of our study is made up by contributions of Paulo Freire, Michael Apple, José Gimeno Sacristán, Boaventura Sousa Santos, Vera Maria Candau, among others, who refer us to an intercultural education. Having the support of the ethics of the liberation by Enrique Dussel, we intend to contribute to an equity that considers the situation of the oppressed by the Other, in line with the principle of otherness.The methodological approach is qualitative, carried out by empirical and documentary research, using the following techniques: questionnaires, a semi-structured interview, content and document analysis. It is hoped that this work may contribute to mitigate prejudice and discrimination against the Bolivian immigrant, which give rise to have them contempted, exploited and expropriated. These atitudes have been historically latent on this frontier, on the grounds of alleged cultural superiority of Brazilians in relation to Bolivians. This investigation may likewise help lend some empowerment of the stigmatized culture and foster the interaction between frontier peoples